Effectiveness of the new polyfunctional infusion solution of blood substitutes on the activity of lipid peroxidation and antioxidant protection of heart in acute fatal blood loss - Ruziev, Umid; Karimov, Khamid; Shevchenko, Larisa; Alimov, Timur (International Journal of Research in Medical Sciences, 2016)
Background: One of the important directions of modern medicine is improving treatment of extreme conditions, the mortality rate of which is still very high, which is often associated with insufficient effectiveness of modern blood substitutes. Purpose of the study was to investigate the efficacy of a new multifunctional blood substitute in acute fatal blood loss on the activity of lipid peroxidation (LPO) and antioxidant system (AOS) of the heart, which showed its high antioxidant efficiency. Methods: Experiment was carried out on 60 rats weighing 180-200 g, clinical death was caused under etaminal anesthesia by acute blood loss from the carotid artery. After bleeding rats were given injection of infusions. Animals were divided into following groups: group I – before blood loss (intact), group II - clinical death, group III (control) – acute fatal blood loss after infusion of saline solution, group IV (comparison) - after acute lethal blood loss with infusion of reo-sorbilact, and group V (main, experimented) - after acute lethal blood loss with the new infusion of multifunctional blood substitute. Results: The level of MDA in clinical death (in group II) had increased by almost 2.0 times, as well as diene ketones, indicators of antioxidant activity decreased. The enzyme activity of GR in heart was 1.2 times lower, GPO - 1.5 times, SOD-2.0 times, catalase-4.4 times. In group III where animals after clinical death were revived with saline solution, AD increased to 45.6±0.4 mm Hg after 1 hour, and CBV increased to 44.8±0.4 ml/kg, the values of these parameters in the intact animals of the first group were 40.2% and 76.6%, respectively. After infusion of saline glomerular filtration rate was 0.61±0.02 ml/min, and diuresis of 0.21±0.02 ml/min compared with the values of these parameters in the intact animals was 46.9% and 65.6%, respectively. Life expectancy of animals after infusion of physiological saline was 12.3±1.2 hours, 30% of the animals survived. After infusion of reosorbilact in group IV, the survival rate was 40%, and after the infusion of a new multifunctional blood substitute in group IV -70%, which is 30% higher Conclusions: The infusion of a new multifunctional blood substitute during acute fatal blood loss leads to a more effective delay of LPO processes and restoration of AOS in heart, in comparison with the use of reosorbilact. The use of a new multifunctional blood substitute during acute lethal hemorrhage in rats, compared with infusion of reosorbilact, leads to a more pronounced recovery of hemodynamic parameters, biochemical parameters of blood and ABS.